Answer:
[tex] {f}^{ - 1} (x) = \frac{1}{8} x + \frac{7}{8} [/tex]
Inverse functions undo the operation of the original function. That is, if x undergoes function f to become f(x), then the inverse function (denoted by f⁻¹) reverse what function f does. Thus, the inverse function of f changes f(x) back into x.
The inverse of a function can be found in 3 main steps, which is to first let y= f(x), then make x the subject of formula before replacing x with f⁻¹(x) and y with x.
Let's apply the above steps to solve the question!
Given: f(x)= 8x +7
Step 1: Let y= f(x).
y= 8x +7
Step 2: Make x the subject of formula.
Start by subtracting 7 from both sides:
8x= y -7
Divide both sides by 8:
[tex]x = \frac{1}{8} y + \frac{7}{8} [/tex]
Step 3: Replace x with f⁻¹(x) and y with x.
[tex] {f}^{ - 1} (x) = \frac{1}{8} x + \frac{7}{8} [/tex]
Additional
To learn more about inverse functions, check out: https://brainly.com/question/19755382